Comment on “A new approach to stabilization of calcareous dune sand” - O'Kelly, Brendan (My University, 2023)
The Discussers read with interest the paper by Ghadr et al. (2022) (the Authors); the research topic being particularly important for various regions of the world regarding the main goals of dust suppression and wind-driven soil erosion control. In their paper, the Authors proposed a new approach for stabilization of dune sand deposits, whereby ground rubber (GR) material and colloidal nano-silica (NS) hydrosol are mixed with the sand, such that a thin, porous and lightweight crustal layer could be formed on the sand deposit for limiting the dust deflation. The Authors report that this GR–NS sand treatment preserves, and may even enhance, the sand’s open pore structure, such that the engineered crustal layer would not disrupt the soil’s biogeochemical cycles. For optimal strength and post-peak performance, the Authors recommend the additions of 5 wt.% GR and 15–25% NS to the test sand (investigating calcareous Urmia Lake sand), whose constituent particles ranged 0.08–3.2 mm in size, as evident from Fig. 2 of their paper.
PUBLISHED
Keywords: Environment; Ecotoxicological; Sand; Stabilization; Tire; Smart & Sustainable Planet; ENVIRONMENT; ENVIRONMENTAL ENGINEERING; Environmental Engineering, Pollution Control; Environmental Geotechnics; Geotechnical Engineering; Geotechnics; SOIL AND WATER CONSERVATION; SOIL CONTAMINATION; SOIL MODIFICATION; Soil Mechanics; Soil Sciences, Conservation; Soil Sciences, Erosion; Soil remediation; Waste tires; bio-geotechnics; geotechnical; soil stabilization; waste tyres